Towards a description of scientific knowledge as a perspective : insights from history of science and science education - Kohler, Alaric (My University, 2015)
Scientific knowledge is commonly considered scientific in relation to its content, to methodological constraints and to a certain quality of reasoning. The scientific knowledge is often considered as corresponding with reality. Studies in science education (e.g. Driver et al. 1996), stress the discrepancies between the way scientific knowledge is taught – mostly in a dogmatic way – and the way it is produced, as it has been described long ago in sociology of science (e.g. Latour & Woolgar, 1979). Current research in science education propose to use argumentation to approach the science in a way closer to its making (Muller Mirza & Perret-Clermont, 2009). From a research on argumentation in physics, we suggest to describe the knowledge to be taught (Tiberghien, 1997) as a specific perspective, or look on the world. Such a description draws on a historico-cultural analysis as proposed by Koyré (1968). References Driver, R., Leach, J., Millar, R., and Scott, P., (1996). Young people's images of science. Open University Press, Buckingham. Koyré, A., (1968). Etudes newtoniennes. Paris: Gallimard. Latour, B., and Woolgar, S., (1979). Laboratory life : the social construction of scientific facts. London : Sage Publication. Muller Mirza, N., and Perret-Clermont, A.N., (2009). Argumentation and Education: Theoretical Foundation and Practices. New York: Springer. Tiberghien, A. (1997). Learning and Teaching: Differentiation and Relation. Research in Science Education, 27, 359-382.
, 16th Biennal Conference of the International Society of Theoretical Psychology « Resistance & Renewal», Coventry, UK
Keywords: perspectivism perspective science education